2021
DOI: 10.3390/diagnostics12010041
|View full text |Cite
|
Sign up to set email alerts
|

Cone-Beam Computed Tomography-Derived Augmented Fluoroscopy Improves the Diagnostic Yield of Endobronchial Ultrasound-Guided Transbronchial Biopsy for Peripheral Pulmonary Lesions

Abstract: Background: Endobronchial ultrasound-guided transbronchial biopsy (EBUS-TBB) is used for the diagnosis of peripheral pulmonary lesions (PPLs), but the diagnostic yield is not adequate. Cone-beam computed tomography-derived augmented fluoroscopy (CBCT-AF) can be utilized to assess the location of PPLs and biopsy devices, and has the potential to improve the diagnostic accuracy of bronchoscopic techniques. The purpose of this study was to verify the contribution of CBCT-AF to EBUS-TBB. Methods: Patients who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…However, uoroscopy can serve the same purpose and increase the accuracy and diagnostic yield. (35,36) While, as previously described, GS had better performance in small lesions, Ito et al (17) suggested that when under uoroscope-guidance, the conventional method could have even better performance.…”
Section: Discussionmentioning
confidence: 86%
“…However, uoroscopy can serve the same purpose and increase the accuracy and diagnostic yield. (35,36) While, as previously described, GS had better performance in small lesions, Ito et al (17) suggested that when under uoroscope-guidance, the conventional method could have even better performance.…”
Section: Discussionmentioning
confidence: 86%
“…Cone-beam computed tomography-derived augmented fluoroscopy (CBCT-AF) is a technique that provides real-time 2-dimensional (2D) fluoroscopy and 3-dimensional (3D) CBCT scans, and has also been used in bronchoscopy procedures [ 4 7 ]. CBCT-AF can guide navigation for the bronchial route, and confirm the location of target PPLs, thereby improving diagnostic accuracy during EBUS-TBB [ 8 , 9 ]. Traditionally, most TBB procedures employed standard biopsy forceps, which frequently obtained small, crushed tissue samples that could affect molecular analysis for further cancer management [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advent of endobronchial ultrasound (EBUS)-guided transbronchial needle aspiration has made it possible to perform a guided biopsy of small PPNs and lesions located near the airways [ 10 ]. However, the diagnostic yield of EBUS for extremely small PPNs is relatively unsatisfactory [ 11 ]. Tools such as a thin bronchoscope and guide sheath or techniques such as fluoroscopy or virtual bronchoscopy navigation have been developed to assist EBUS-guided biopsy in increasing diagnostic yield.…”
Section: Introductionmentioning
confidence: 99%
“…Tools such as a thin bronchoscope and guide sheath or techniques such as fluoroscopy or virtual bronchoscopy navigation have been developed to assist EBUS-guided biopsy in increasing diagnostic yield. Nevertheless, some limitations still demonstrate the necessity for more effective systems [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation